Intercultural Communicative Competence: Why Is It Significant and How Can It Be Enhanced in EFL Settings? - Akyıldız, Seçil Tümen; Çelik, Vildan; Ahmed, Kwestan Hussein (My University, 2021)
In the current literature on foreign language teaching, it has become clear that having the requisite ability ofintercultural communicative competence (ICC) to be aware of different cultures, respect them, and interact with people fromdifferent cultures is crucial. Language is connected to culture and societies, in which people need to communicate with oneanother. English as a lingua franca provides a means of communication among different cultures. Thus, English as a foreignlanguage (EFL) teaching classes offer perfect situations to foster ICC. From this viewpoint, this article gives an account toraise awareness of ICC in EFL settings by explaining ICC and its relationship with language, describing the significance ofICC, and illustrating some suggestions in the literature for the enhancement of ICC in EFL classes. This paper seeks to improveEFL teachers’ understanding of intercultural communication and to help them with their classroom practices.
Keywords: Eğitim; Eğitim Araştırmaları